EVALUASI PELAKSANAAN TANGGUNG JAWAB SOSIAL PT. ADIRA FINANCE DI KELURAHAN SATRIA KECAMATAN BINJAI KOTA KOTA BINJAI - Barham Siregar (Universitas Medan Area, 2019)
Development, in addition to the positive impact also brought environmental disaster for many because the environment is considered as an object that connotes commodities and continue to be exploited without taking into account the carrying capacity of the environment. One of the efforts to improve the environmental balance is through a program of Corporate Social Responsibility (CSR). Corporate Social Responsibility (CSR) which is the formulation of research problems is the implementation of the implementation of Corporate Social Responsibility (CSR) as the social capital of PT. Adira Finance, how assessment Corporate Performance Assessment Program (PROPER) on Corporate Social Responsibility (CSR) PT. Adira Finance and favorable factors and inhibiting the implementation of Corporate Social Responsibility (CSR) PT. Adira Finance.This type of research is descriptive qualitative. Primary data were obtained from interviews and questionnaires to the 40 members of the public and direct observation.In implementing CSR PT. Adira Finance has been working on the preservation of the environment, support environmental awareness programs. And for CSR activities conducted in the Village District Satria Binjai City PT. Adira Finance held a reforestation program to plant 400 mahogany trees.